الدراسة الجامعية للطالبة المتزوجة وانعكاساتها على حياتها الاجتماعية - لبيهي, خديجة (جامعة الوادي university of Eloued, 2022)
الملخص: تهدف هذه الدراسة إلى معرفة انعكاسات الحياة الاجتماعية على دراسة الطالبة الجامعية المتزوجة، في جامعة الوادي، وركزت الدراسة على الانعكاسات التالية (الرعاية التامة للأبناء- العمل المنزلي – تفهم الزوج)، وقد تم طرح التساؤل الرئيسي التالي: هل تؤثر الدراسة الجامعية للطالبة المتزوجة على حياتها الاجتماعية؟ ويتفرع من هذا التساؤل التساؤلات الفرعية التالية: - هل تواجه الطالبة الجامعية المتزوجة أعباء في الرعاية التامة بأبنائها؟ - هل تواجه الطالبة الجامعية المتزوجة صعوبات في القيام بشؤونها المنزلية اليومية؟ - هل تواجه الطالبة الجامعية المتزوجة صعوبة في تفهم الزوج للدراسة؟ وللدراسة أهمية تتجلى من خلال: لقد أجرينا الدراسة في جامعة الشهيد حمه لخضر الوادي "كلية العلوم الاجتماعية والإنسانية "ولاية الوادي وتتمثل الدراسة في دراسة الجامعية للطالبة الجامعية ولانعكاساتها على حياتها الاجتماعية، حيث التجأتا الباحثتان إلى المنهج الوصفي التحليلي ،حيث يهتم يهتم هذا المنهج بالبحث عن أوصاف الظاهرة المراد دراستها من خلال جمع الحقائق والبيانات وتصنيفها وتبويبها ،وقد تمت الدراسة على 50طالبة متزوجة تزاول دراستها بجامعة الشهيد حمه لخضر الوادي .أما بالنسبة لأداة جمع البيانات لقد تم الاعتماد على الاستبيان "الاستمارة " حيث تمكننا من جمع المعلومات الكافية على المبحوثين. وتتجلى أهمية هذه الدراسة في النقاط التالية: 1. هذه الدراسة تحاول إبراز تأثير دراسة الطالبة الجامعية المتزوجة وانعكاساتها على حياتها الاجتماعية. 2. تحاول الدراسة تقديم بعض الحلول التي تساهم في فهم وضع دراسة الطالبة الجامعية المتزوجة لتحسين انعكاساتها على حياتها الاجتماعية. 3. معرفة العراقيل والصعوبات التي تواجه الطالبة الجامعية المتزوجة في مسارها الدراسي. وقد توصلت الدراسة إلى النتائج التالية:  تنعكس دراسة الطالبة المتزوجة إيجابا وسلبا على تربية أبنائها.  تنعكس دراسة الطالبة المتزوجة سلبا على القيام بشؤونها المنزلية اليومية.  تنعكس دراسة الطالبة الجامعية المتزوجة إيجابا على صعوبة تفهم الزوج وضعها الدراسي. Abstract: This study aims to find out the reflections of social life on the study of a married female university student, at the University of EL OUED, and the study focused on the following reflections (the full care of children – the house work – the understanding of the husband), and the following main question was raised: Does a married female student's university studies affect her social life? The following sub-questions are derived from this question: Does a married female university student face burdens in the full care of her children? Does a married female university student have difficulties in doing her daily house work? - Does a married female university student have difficulty with the husband understanding her study? The study has an importance manifested by: The importance of any study known as the practical and scientific solutions provided by the researcher to the problem at hand derives its importance from the nature of the sample used: married females students who have become a high percentage of the university community, because the woman study ads a beautiful developing touch, as it achieves additional gains that will cast a shadow in the future on the self-empowerment of women and on the family and society, and show the right of women to education as they represent half of society, and give them the opportunity to prove themselves and expression in her opinion and the development of herself and her ability towards her society and towards a better life for her and her family, this study derives its importance from the nature of the subject where it drains the effort of the students in order to achieve the required balance. 1. This study tries to highlight the impact of the study of a married female university student and its reflections on her study life. 2. The study tries to provide some solutions that contribute to understanding the status of the study of a married female university student to improve her reflections on her social life. 3. Knowing the obstacles and difficulties faced by a married female university student in her studying journey. The study reached the following conclusions:  The study of the married female student reflects positively and negatively on the upbringing of her children.  The study of a married female student reflects negatively on her daily house work.  The study of the married university student reflects positively on the difficulty of the husband understanding her study situation.
دراسة ميدانية على قسم العلوم الاجتماعية والانسانية
مذكرة ماستر علم اجتماع تخصص علم الاجتماع التربية
Keywords: الطالبة الجامعية المتزوجة، التحصيل الأكاديمي، عمل المرأة; Étudiant universitaire marié, réussite scolaire, travail féminin; Married university student, academic achievement, women's work